Sex-dependent differences in the in vivo respiratory phenotype of the TASK-1 potassium channel knockout mouse - Jungbauer, Stefan; Heitzmann, Dirk (Respiratory physiology & neurobiology, 2017)
TASK-1 potassium channels have been implicated in central and peripheral chemoreception; however, the precise contribution of TASK-1 for the control of respiration is still under debate. Here, we investigated the respiration of unrestrained adult and neonatal TASK-1 knockout mice (TASK-1−/−) using a plethysmographic device. Respiration in adult female TASK-1−/− mice under control (21% O2), hypoxia and hypercapnia was unaffected. Under acute hypoxia male TASK-1−/− mice exhibited a reduced increase of the respiratory frequency (fR) compared to wildtypes. However, the tidal volume (VT) of male TASK-1−/− mice was strongly enhanced. The volatile anesthetic isoflurane induced in male TASK-1−/− and male wild type mice (TASK-1+/+) a similar respiratory depression. Neonatal TASK-1−/− mice demonstrated a 30-40% decrease of the minute volume, caused by a reduction of the fR under control condition (21% O2). Under hypoxia, neonatal TASK-1−/− mice more frequently stopped breathing (apnea>3s) suggesting an increased hypoxia-sensitivity. As reported before, this increased hypoxia sensitivity had no influence on the survival rate of neonatal TASK-1−/− mice. In adult and neonatal mice, TASK-1 gene deletion induced a significant prolongation of the relaxation time (RT), which is a parameter for expiration kinetics. Additionally, screening for mutations in the human TASK-1 gene in 155 cases of sudden infant death syndrome (SIDS) was inconclusive. In conclusion, these data are suggestive for an increased hypoxia-sensitivity of neonatal TASK-1−/− mice, however, without causing an increase in neonatal lethality. In adult female TASK-1−/− mice respiration was unaffected, whereas adult male TASK-1−/− mice showed a modified breathing pattern. These results are suggestive for sex-specific mechanisms for compensating the inactivation of TASK-1 in mice.
Gesehen am 21.06.2018
Available online 10 November 2016